Newly qualified South African teachers : staying or leaving? : research article - Bertram, Carol; Wedekind, Volker; Muthukrishna, Nithi (Perspectives in Education, 2007)
The international recruitment by countries of the North of teachers from less developed countries has become a controversial aspect of the problem of 'brain drain'. As a political and economic issue, the argument is that it reduces human capital within the education system and leads to the movement of highly skilled teachers from countries that can least afford to lose them. In South Africa the issue of teacher mobility is more complex because opinion is divided on the extent of the problem, what the trends are, and how best to assess what is going on. There is also no reliable data on how many teachers the country loses to international recruitment. This article presents a study that explored the career plans of a sample of final year students who graduated at the end of 2004 and 2005. The study drew from two large-scale survey questionnaires of final year student teachers from eleven higher education institutions (HEI) in 2004 and fourteen HEIs in 2005. The study found that 27.4% of the 2004 sample and 23.4% of the 2005 sample had indicated that they were definitely going to teach abroad or were considering teaching abroad. Age, race and teaching phase are significant variables in the decision to teach abroad. For the 2004 sample, white and Indian teachers, primary teachers and teachers from particular institutions are more likely to choose to teach abroad. For the 2005 sample, white, BEd Foundation phase students who are younger than 27 years are the most likely to choose to teach abroad. However, it appears that the majority of teachers are planning to return to South Africa, perhaps signifying a 'brain circulation', rather than a 'brain drain'.
Keywords: openalex:import

The career plans of newly qualified South African teachers - Bertram, Carol; Appleton, Simon; Muthukrishna, Nithi; Wedekind, Volker (South African Journal of Education, 2006)
We report on survey data collected from 776 final-year student teachers from 11 higher education institutions in October 2004. The purpose of the survey was to find out how many newly qualified teachers were planning to teach abroad and how many were planning to teach in South Africa. Two issues formed the backdrop of the study: teacher migration and teacher shortages in South Africa. Key findings from the study showed that 27.4% of the student teachers were planning to teach abroad in 2005, 63.3% were planning to teach in South Africa, and the remainder (7.2%) were not planning to teach. However the vast majority of those planning to teach abroad indicated that they would be returning to South Africa within two years. Of the student teachers who were planning to teach in South Africa, only 33% indicated that they already had a job secured for 2005. Three-quarters of these posts were to be paid by school governing bodies in ex-Model C schools. We argue that teacher shortages are not translating into available jobs for newly qualified teachers. Issues of race cannot be ignored, in that white teachers are more likely to get posts in well-resourced schools, and are more likely to go abroad to teach.
Keywords: openalex:import